2019
DOI: 10.1111/dth.12881
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diabetes and metabolic syndromes to the effectiveness of cyclosporine a pharmacotherapy in psoriatic patients

Abstract: Metabolic diseases concurrent with psoriasis may considerably affect the intensity of its symptoms and therapy efficacy. Cyclosporine A (CsA) is one of the medicines used in conventional therapy of psoriasis. The aim of the study was to determine whether Diabetes 2 and metabolic syndromes influence the efficacy of the CsA therapy in psoriatic patients. The sample group was composed of 32 patients with diagnosed moderate to severe forms of psoriasis vulgaris. The group was divided into subgroups, with regard to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Michalska-Bańkowska et al, observed that concommitant diabetes and a metabolic syndrome did not affect the efficacy of cyclosporine in psoriasis treatment. However, in the study they included thirty-two patients with psoriasis vulgaris, of which seven had coexisting diabetes mellitus, seven patients had both diabetes and metabolic syndrome, and the remaining patients had no comorbidities [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Michalska-Bańkowska et al, observed that concommitant diabetes and a metabolic syndrome did not affect the efficacy of cyclosporine in psoriasis treatment. However, in the study they included thirty-two patients with psoriasis vulgaris, of which seven had coexisting diabetes mellitus, seven patients had both diabetes and metabolic syndrome, and the remaining patients had no comorbidities [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the research conducted by Michalska-Bańkowska et al ., which evaluated the changes in TGF-β1, TGF-β2 and TGF-β3 expression under the influence of cyclosporine A, although the method of handling the test samples was analogous to that described in our own study, other relationships in the transcriptional activity occurring after administration of the drug may be noticed. In the study on cyclosporine A, the expression of both TGF- β 1 and TGF- β 2 after 42 days (6 weeks) decreases, so that in the next stage, it will slightly increase [ 21 ]. On the other hand, in the case of TGF- β 3 , an increase in expression was initially observed, which decreased after 42 days.…”
Section: Discussionmentioning
confidence: 99%
“…In a small group of patients with moderate to severe psoriasis, comorbidity with diabetes or metabolic syndrome did not affect the efficacy of cyclosporin. 93 In another clinical study, cyclosporin significantly improved patients’ psoriasis symptoms and this was associated with increased transcription activity of TGFβ1 at the end of treatment in those with or without diabetes, and with or without metabolic syndrome. 112 Through inhibition of the enzyme cyclophilin, cyclosporin has shown beneficial effects on liver fibrosis and cirrhosis in some patients.…”
Section: Hepatic Effects Of Systemic Psoriasis Treatmentsmentioning
confidence: 95%
“…The effects of CYC on TGFβ levels was determined in PSO pts treated for 12 weeks CYC significantly improved PSO symptoms and QoL of pts in this 3-month clinical study. CYC also increased the transcription activity of TGFβ1 at the end of treatment in pts with or without diabetes, and with or without metabolic syndrome [ 93 ] APR Assessment of efficacy, safety and metabolic biomarkers in 113 pts with PSO and/or PsA treated with APR for 1-year Pts with diabetes treated with APR achieved better clinical benefit for their PSO (extent and severity) compared with non-diabetic patients. In addition, after 1 year, blood glucose levels and LDL-C levels were significantly reduced by APR [ 94 ] Effects on inflammatory biomarkers: biological agents ADA A 12-week RCT comparing the effects of ADA, PHO and PLA on vascular inflammation and markers of lipid and glucose metabolism, and inflammation in pts with moderate to severe PSO.…”
Section: Hepatic Effects Of Systemic Psoriasis Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation